Study on Diversity of Sapodilla (Manilkara zapota) by Molecular Marker in the Special Region of Yogyakarta - Vega Kartika Sari; Rani Agustina Wulandari; Rudi Hari Murti (AGRIVITA, Journal of Agricultural Science, 2018)
The objective of this research was to determine the diversity and relationship of sapodilla accession derived from districts in DIY based on DNA profiles. From the screening of 20 total primers, five primers (OPA 20, OPB 5, OPB 6, OPB 8, and OPC 19) producing polymorphic bands in RAPD analysis were selected. Different-shaped samples of sapodilla randomly collected from Bantul, Gunungkidul, Kulonprogo, Sleman and Yogyakarta city were used in this research. The analysis of molecular data was performed by using NTSys pc-2.02 and GenAlex 6.1 program. The clustering indicated that the accessions tend to group by their locations. However, there was no corelation between DNA marker and the fruit shape. The first group comprised samples from Yogyakarta city (Keraton Yogyakarta), Bantul and Kulonprogo while the second group consisted of samples from Sleman and Gunungkidul with genetic similarity of 53% and 37% respectively. The genetic diversity was high (PLP = 98.85% of 87 loci and H=0.280±0.14) comprising the genetic diversity within population (53%) which was greater than genetic diversity between populations (47%). Having the highest genetic diversity, Gunungkidul should be potential for conservation and selection of sapodilla in DIY.